Experience of sexual harassment & challenges for nurses in public & private hospitals - Malik, Subha; Iftikhar, Mahnoor; Zafar, Maryam (Journal of Pakistan Psychiatric Society, 2021)
ObjectiveA comparative study was conducted to examine reasons behind psycho-social challenges and violence/harassment related issues faced by female nurses in different public and private hospitals in Lahore, Pakistan.Study DesignMixed Method Correlational researchPlace and duration of the study The study was conducted during March-May 2019 at public hospitals and private hospitals of Lahore.Subject and MethodSexual Harassment Experience questionnaire was used for quantitative analysis for which 250 female nurses from public/private hospitals were contacted. For qualitative analysis two focus group discussions were conducted on a sample of 20 female nurse participants, 10 each from public and private hospital.Results: Quantitative analysis showed that private hospital nurses are facing more gender harassment, sexual attention and sexual coercion as compared to nurses in public hospital. The thematic analysis revealed four major themes comprising of factors effecting performance, lack of facilities, coping tactics and psychosocial issues.Conclusion: In a culture where giving voice to sexual harassment turns into stigma, it is difficult for nurses to report their problems which can influence their professional or personal growth.